Student Literacy Competence in Science Learning in Junior High Schools with the Reading to Learn Model - Yanti - Fitria; Dwi Suryani Alfa; Muhammad Irsyad; Muhammad Anwar; Qotrun Nada Fitri Adisva; Habbieb Abdullah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The current era of globalization has succeeded in creating various problems and challenges of human life. The ability to solve problems and challenges of life is very necessary. The place for education, especially science, is the main key so that citizens are able to live their lives well. The phenomenon of the low mastery of integrated science content of students at the basic education level cannot be separated from the dimensions of their literacy attitude. These dimensions include the application of science, knowledge of science, the process of science, and patterns of behavior towards science. The aim of this study was to describe the scientific literacy skills of students in learning with factual texts. The type of research used is descriptive qualitative research. A total of 40 students were used as sources of information to view and obtain a literacy competency profile in science learning. Data were collected through observation and tests through a number of questions to obtain information on the dimensions of students' literacy attitudes. The research finding is that there is an increase in learning progress based on the results of the pretest and posttest with a difference of 15.8 points for the overall PISA competency aspect. The competence aspect of explaining scientific phenomena obtained the lowest average result, while the competence aspect of evaluating and interpreting the data obtained a higher average result. Thus, it can be concluded that the implementation of science learning in schools should be more meaningful for students so that they are able to have higher literacy skills, especially scientific literacy. This can be achieved by applying holistic and integrative learning in science learning